MARGINALISASI GAMELAN BATEL DALAM SENI PERTUNJUKAN WAYANG KULIT DI DESA SIBANGGEDE, KABUPATEN BADUNG - I Nyoman Surianta (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
The marginalization of the Gamelan Batel in Sibanggede Village can be observed in the form of the decrease of the traditional art values in the society, the displacement of traditional arts, the seculariza- tion of the traditional art, the narrowing of the traditional art performances, the hegemony of the modern art to that of the traditional one. Second, there are two factors that cause the Gamelan Batel in Sibanggede Village to be marginalized, namely, internal and external factors. The internal factors include lack of talent, lack of public interest, lack of open attitude, lack of funding from the govern- ment. The external factors are economics, technology and information, the function shift of the tradi- tional gamelan. Third, the impact of the marginalization of the Gamelan Batel in Sibanggede Village is in the form of the failure to form regeneration, failure of reconstruction effort, failure of revitalization effort.